WESTERN BALKANS U. S. POLICY IN THE CONTEXT OF THE PRESIDENT TRUMP’S GRAND STRATEGY - Dragan Simić; Dragan Živojinović (Srpska Politička Misao)
Many critics of Donald Trump argue that Donald Trump’s Grand Strategy is an absence of Grand Strategy or that his foreign and security policy is driven by impulses and tactical approach. However, such policy leaves us with practical consequences which mean that we have to follow this sort of a Donald Trump approach to foreign affairs and politics in general. The best guide in that sense would be the 2017 U. S. National Security Strategy idea of principled realism which is the most important written strategic statement of the Trump administration up to this date. If Trump’s approach “is guided by outcomes not ideology” and if “prosperity depend on strong, sovereign nations that respect their citizens at home and cooperate to advance peace abroad”, then the U. S. policy to Western Balkans has to be considered in that context. The Prespa agreement between Greece and North Macedonia is one form of that approach put in practice. Having in mind Belgrade–Pristina negotiations and Bosnia and Herzegovina’s future as well, the main thesis of this paper is that we may expect some kind of unusual approach from the United States to this region, different from the framework that was set up in the 1990s. That will have consequences both for the region and for the outside great powers, especially the European Union.